Evaluation of some technical indicators with the use of the plow on clay soil. - ezzy, Mohanad S. Al; Almayyahi, Asaad Kh. (International Journal of Psychosocial Rehabilitation, 2020)
The experiment carried out on clay soil from Diyala city in 2019, the experiments were included using tractor type (New Holland T7.185) with a chisel plow by changing the speed of the tractor and the plowing depth in the clay soil.Three plowing speeds were selected for tractor (0.888, 1.322, 1.744 m/sec) and variable plowing depth (0.14, 0.18,0.225 m) with technical indicators which included:Draft force of tractor, practical productivity, Soil Volume Disturbed and fuel consumption.The experiments were carried out in experimental method and in four repeated cases.Statistically, the differences were tested in the least moral difference level (0.05).According to the complete random design, based on the devices testing, we can conclude that the results of the experiments werereliable.It was found that the increase plowing speed of the tractor led to increased Draft force of tractor, practical productivity, soil volume disturbed and fuel consumption, also was found that increasing plowing depth leads to increasing draft force of tractor, decreasing practical productivity, increasing soil volume disturbed and fuel consumption.The plowing depth (0.14 m) exceeded the plowing depths (0.18,0.225 m) in achieving the lowest draft force of (2.542 KN) and the highest , practical productivity (1.438 m2/sec), while the working speed of the tractor (0.888 m/sec) exceeded In achieving the lowest draft rate of (2.796 KN) and the lowest practical productivity (0.94 m2/sec) and the lowest Soil Volume Disturbed (0.169 m3/sec) and the lowest fuel consumption (0.00161 L/sec), as for the practical speed of the tractor (1.744 m/sec) It exceeded the speed (0.888, 1.322 m/sec) in achieving the highest practical productivity (1.883 m2/sec) at the plowing depth (0.14 m).